A 3D modelling on RC beams strengthened externally by Mengkuang Leaves-Epoxy Composite Plate: finite element analysis - Muhammad Ibrahim, Adham Ghazali (2018)
The research presents a finite element analysis modelling to investigate the behaviour of reinforced concrete beam strengthened externally using Mengkuang Leaves-Epoxy Composite Plate (MLECP). ANSYS CivilFEM 12.0 is used in this research. The major objectives of the research are to study the structural behaviour of reinforced concrete beams strengthened with MLECP at the flexural zone in terms of load deflection behaviour, crack pattern, failure mode by using finite element analysis and validate the result with experimental result, besides, to determine the effective strengthening method between surface-wrap and U-wrap. A total of three (3) beams with dimension of 100 mm width, 130 mm height and 1600 mm length were modelled as simply supported beams in three-dimensional (3D). The beams were modelled symmetrically. Two types of strengthening methods were used which included surface strengthening and U-wrap strengthening. U-wrap strengthening method was modelled based on validation of control beam and surface wrap strengthening method. The most effective strengthening method was determined from the numerical modelling. Based on the numerical result, all beams failed in shear at reasonable load. By comparing with the control beam, surface and U-wrap strengthening methods have resulted into an increment in the beam bearing capacity by 10% and 15%, respectively. As for the deflection, control beam, U-wrap and surface strengthening method recorded decreasing in value which is 7.48 mm, 6.55 mm and 6.07 mm, respectively. A comparison between the numerical and experimental results showed that a comparable agreement on the load deflection behaviour and strong agreement on the crack patterns. The most effective strengthening method is U-wrap method.